Ease of Commercialization and Downstream Processing of Ginger-Processed Products - Ida Rosada; St. Sabahannur; Rasmeidah Rasyid Patingari; Nursyamsuryani Nursyamsuryani (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
This research aims to analyze the input of raw materials and other inputs, receipts, and benefits, and analyze the added value of processed ginger products as herbal drinks. The processed ginger products analyzed are the syrup drink